Equine lung decellularization: a potential approach for in vitro modeling the role of the extracellular matrix in asthma. (November 2018) - Palma, Renata Kelly da; Fratini, Paula; Schiavo Matias, Gustavo Sá; Cereta, Andressa Daronco; Guimarães, Leticia Lopes; Anunciação, Adriana Raquel de Almeida; de Oliveira, Luis Vicente Franco; Farre, Ramon; Miglino, Maria Angelica
Contrary to conventional research animals, horses naturally develop asthma, a disease in which the extracellular matrix of the lung plays a significant role. Hence, the horse lung extracellular matrix appears to be an ideal candidate model for in vitro studying the mechanisms and potential treatments for asthma. However, so far, such model to study cell–extracellular matrix interactions in asthma has not been developed. The aim of this study was to establish a protocol for equine lung decellularization that maintains the architecture of the extracellular matrix and could be used in the future as an in vitro model for therapeutic treatment in asthma. For this the equine lungs were decellularized by sodium dodecyl sulfate detergent perfusion at constant gravitational pressure of 30 cmH2 O. Lung scaffolds were assessed by immunohistochemistry (collagen I, III, IV, laminin, and fibronectin), scanning electron microscopy, and DNA quantification. Their mechanical property was assessed by measuring lung compliance using the super-syringe technique. The optimized protocol of lung equine decellularization was effective to remove cells (19.8 ng/mg) and to preserve collagen I, III, IV, laminin, and fibronectin. Moreover, scanning electron microscopy analysis demonstrated maintained microscopic lung structures. The decellularized lungs presented lower compliance compared to native lung. In conclusion we described a reproducible decellularization protocol that can produce an acellular equine lung feasible for the future development of novel treatment strategies in asthma.